Fabrication of graphene oxide/inulin impregnated with ZnO nanoparticles for efficient removal of enrofloxacin from water: Taguchi-optimized experimental analysis. (15th September 2022) - Rahman, Nafisur; Raheem, Abdur
Abstract: A novel nano-adsorbent zinc oxide impregnated graphene oxide/inulin (ZGI) was prepared for the investigation of the removal efficiency of enrofloxacin. Characterization of the nano-adsorbent was accomplished through Fourier transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled with EDS, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The average crystallite size of nanomaterial (ZGI) calculated from XRD data was 14.82 nm. The adsorption of enrofloxacin onto ZGI was performed in batch mode. The variables of adsorption process such as adsorbent dose, pH, contact time and initial concentration of enrofloxacin were optimized by Taguchi method to achieve the maximum removal efficiency. The optimum values of variables were: adsorbent dose = 25 mg, pH = 7, contact time = 60 min and initial concentration = 50 mg/L. The maximum adsorption capacity and removal efficiency of the material for enrofloxacin were 317.83 mg/g and 98.60%, respectively at 303 K. Redlich-Peterson isotherm model was the best fitted among the various isotherm models based on highest R 2 values (0.9978–0.9981) and lowest χ 2 (3.43 × 10 − 4 − 2.00 × 10 − 3 ) . Kinetic data followed pseudo-second order model (R 2  ≥ 0.9974) more accurately as compared to pseudo-first order model (R 2 ≤ 0.9772 ) . The adsorption mechanism was illustrated on the basis of XPS and Raman studies. Reusability investigation showed that the nano-adsorbent ZGI could be used up to 5 adsorption-desorption cycles with greater than 90% removal efficiency. Graphical abstract: Image 1 Highlights: Impregnation of ZnO into graphene oxide/inulin (ZGI) increased the adsorption capacity for enrofloxacin. Taguchi method was used to optimize the controllable factors of adsorption process. Maximum enrofloxacin sorption capacity (317.83 mg/g) reached in 6° min. ZGI had good reusable performance up to 5 adsorption-desorption cycles with >90% removal efficiency.